Modeling the Glomerular Filtration Barrier and Intercellular Crosstalk - Ebefors, Kerstin; Lassén, Emelie; Anandakrishnan, Nanditha; Azeloglu, Evren U.; Daehn, Ilse S. (Frontiers in Physiology, 2021)
The glomerulus is a compact cluster of capillaries responsible for blood filtration and initiating urine production in the renal nephrons. A trilaminar structure in the capillary wall forms the glomerular filtration barrier (GFB), composed of glycocalyx enriched and fenestrated endothelial cells adhering to the glomerular basement membrane and specialized visceral epithelial cells, podocytes, forming the outermost layer with a molecular slit diaphragm between their interdigitating foot processes. The unique dynamic and selective nature of blood filtration to produce urine requires functionality of each of the GFB components, hence mimicking the glomerular filter in vitro has been challenging, though critical for various research applications and for drug screening. Research efforts in the past few years have transformed our understanding of the structure and multifaceted roles of the cells and their intricate crosstalk in development and in disease pathogenesis. In this review we present a new wave of technologies that include glomerulus-on-a-chip, three-dimensional microfluidic models, and organoids all promising to improve our understanding of glomerular biology and to enable the development of GFB targeted therapies. Here, we also outline the challenges and the opportunities of these emerging biomimetic systems that aim to recapitulate complex glomerular filter, and the evolving perspectives on the sophisticated repertoire of cellular signaling that comprise the glomerular milieu.